Erosion and Renewal of Professional Powers in Public Sector Employment: The Role of Occupational Community - Campbell, Shelagh (Relations industrielles / Industrial Relations, 2014)
SummaryThis paper describes a case study of a particular form of knowledge worker; lawyers, and their efforts to achieve collective bargaining. Within self-regulated professions like law, the professional regulatory body controls much of the labour process and defines the body of professional knowledge. Apprenticeships, such as clinical locums in medicine and articles in law, play an important role in the transfer of labour process norms. However, more and more professionals seek employment in large organizations where the autonomy historically enjoyed by the self-employed worker and crafted in the confines of mentorships is increasingly subject to bureaucratic and administrative controls. In large employment settings rules and policies may interfere with workers’ exercise of professional discretion and full utilization of their knowledge. The result of the erosion of traditional labour process power under bureaucratic forms of organization leads professionals to seek alternate forms of control. Many turn to collective bargaining as a mean to wrest back control over the application of discretionary judgment from large, often public sector, employers.In the case of the legal profession in Canada, a great many lawyers are employed in the public sector. The subspecialty of criminal prosecution was broadly framed as a service private sector lawyers once provided on a fee-for-service basis, but until relatively recently it was not a distinct area of practice to which one dedicated a career. The regularization of prosecution in the public sector results in a strong sense of occupational community among public prosecutors. The forces of bureaucratic control and occupational community act together to support collective bargaining among professionals who otherwise have been opposed to this strategy, claiming it is “unprofessional”.